Identification of chalcone isomerase family genes and roles of DnCHI1 in flavonoid metabolism in Dendrobium nobile - Chang, Ling-ling; Zhou, Yu-xin; Wang, Ling-rong; Liu, Lei; Li, Zhen-jian (Frontiers in Plant Science, 2025)
Dendrobium nobile is a prized orchid species with both medicinal and ornamental values, known for accumulating flavonoids that contribute to its bioactivity and flower pigmentation. Chalcone isomerase (CHI), a key enzyme in the flavonoid biosynthetic pathway, catalyzes the conversion of chalcone to naringenin, thereby promoting the production of anthocyanins and other flavonoids. In this study, we present the first systematic analysis of the CHI gene family in D. nobile, classifying them into two subfamilies. Expression profiling revealed that DnCHI1, a type IV CHI, is highly expressed in petals, suggesting a potential role in anthocyanin metabolism. Heterologous transient overexpression assays showed that DnMYB90 significantly downregulated endogenous PeCHI expression and reduced anthocyanin accumulation, whereas DnCHI1 overexpression resulted in a 15-fold increase in anthocyanin content. Dual-luciferase reporter and yeast one-hybrid assays further confirmed that DnMYB90 acts as a transcriptional repressor of DnCHI1. These results provide new insights into the regulatory module in anthocyanin biosynthesis in D. nobile, highlighting the functional divergence of CHI genes and their interaction with MYB transcription factors.